2017
DOI: 10.1002/ep.12783
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization of miscanthus and its application in heavy metals removal from wastewaters

Abstract: Miscanthus species originated in Asia and were imported into Europe and North America as ornamental plants. They are perennial rhizomatous grasses with lignified stems and present very high growth rates, even in more temperate maritime climates. This potentially abundant biomass offers benefits to many sectors and is used to an extent in energy generation applications, however, issues with regards to its physicochemical combustion characteristics currently hinder this uptake. In this work, a novel alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 49 publications
5
17
0
Order By: Relevance
“…The DMP showed a typical lignocellulosic biomass composition of 41-45 wt.% C, 5.7-5.9 wt.% H, 1.2-1.8 wt.% N and 47-50 wt.% O along with a minor contribution of sulphur ~0.2 wt.%, this is in agreement with the previous publication 30 . The SEM images of the DMP in previous work showed large fibrils arranged in the fascicular texture form 30 . Figure 3 shows the SEM images of the ACs either with phosphoric acid (AC-P) or potassium hydroxide (AC-K) along with the CNTs at a different level of magnifications using the ETD detector.…”
Section: Results and Discussion Of Lignocellulosic Biomass Characterisupporting
confidence: 92%
“…The DMP showed a typical lignocellulosic biomass composition of 41-45 wt.% C, 5.7-5.9 wt.% H, 1.2-1.8 wt.% N and 47-50 wt.% O along with a minor contribution of sulphur ~0.2 wt.%, this is in agreement with the previous publication 30 . The SEM images of the DMP in previous work showed large fibrils arranged in the fascicular texture form 30 . Figure 3 shows the SEM images of the ACs either with phosphoric acid (AC-P) or potassium hydroxide (AC-K) along with the CNTs at a different level of magnifications using the ETD detector.…”
Section: Results and Discussion Of Lignocellulosic Biomass Characterisupporting
confidence: 92%
“…The ultimate analysis of PPW showed a wt% of carbon, hydrogen, nitrogen and sulphur of 41.9, 5.6, 1.6 and < 0.3 wt%, respectively. The results are in agreement with the previous publication which showed that the typical composition of lignocellulosic biomass is approximately 41-45 wt% C, 5.7-5.9 wt% H, 1.2-1.8 wt% N and 0.2 wt% S (Osman et al 2018). During the production of ACs and CNTs, the wt% of carbon significantly increased to approximately 70 wt%, which is in agreement with the EDX results shown in Table 1.…”
Section: Sbet(m 2 G -1 )supporting
confidence: 92%
“…4 for raw PPW and CNTs samples at multiple heating rates under a nitrogen atmosphere. The holocellulose components decompose easier than lignin in general; where hemicellulose and cellulose decompose in the temperature range of 200-375°C and 275-380°C, respectively, whereas lignin decomposes at a temperature range of 180-550°C (Osman et al 2017, Osman et al 2018. Liang et al reported that PPW showed a thermal decomposition that was in the temperature range of 200-500°C, where herein, it was in the temperature range of 217-500 o C (Liang &McDonald 2014).…”
Section: Tga/dtg Analysismentioning
confidence: 99%
“…The use of clays as low-cost adsorbents is in accordance with the directions for mining waste management indicated in directive 2006/21/EC on the management of waste from extractive industries [20]. There is also a noticeable trend of using natural materials in adsorption, including both waste rocks [21] as well as agricultural waste materials [22]. The clays as well as other materials are often modified thermally [23,24] or chemically [25][26][27] to enhance their adsorptive properties.…”
Section: Introductionmentioning
confidence: 91%